MOTIVASI DAN PROSES PENCIPTAAN TARI ANAK DI SANGGAR TARI KEMBANG SORE - Trie Wahyuni (LPPM UNY, 2009)
The research was aimed to describe the form of presentation, to learn the motivation of children dance creator behind his works with animal theme, and to explore the dance creation processes produced by Kembang Sore Dance Gallery (STKS). The research performed at Yogyakarta on May-October 2007 in qualitative approach. Subject of the research: dance creator produced by STKS, dance instructor, dance wardrobe crew produced by SKTS, STKS members. Data was obtained technically by: observation, documentation study, and deep interview. The results show: Dance works produced by SKTS with animal theme was originated from idea expanding from the imagination of the creator to give the education about animal world to the early children, elementary school, and junior high school. On the other hand, to fulfill dance teachers request joined in children dance training to give teaching materials about animal worlds to the early children, elementary school, and junior high school. The dance work was categorized into new creation dance form. Creation process used creative process includes some steps they are, investigation exploration directly to the observation object, make improvisation trying possible movements can be expressed suitable with the movement characteristics of early children, elementary school, and junior high school. Sorting evaluation of the movements has been found was adapted with dance theme. Movement sequences created by STKS consisted of 3 components, namely a beginning movement that the moving sequences was improved in intermediate level, sitting movement that the moving sequences was performed in sitting (low level), and the movement after sitting that the moving sequences was performed in intermediate level. All of the components were combined into the harmonic unity, with the repeat of movement, rhythm, realized to give the variation and clarity of design from was shaped of several moving position. The movement dynamics consistent with the tap/accentuation of the accompanied music was arranged and using kendang directly drummed by Untung Mulyono. Person who listen the voice of tabuhan accompanied the dance at a glance will realize the East Java taste. The dynamics of the dancing movement united with the kendang dynamics was drummed by the creator, gives the dynamics and rhythmic tastes. Every dance movements he was created always followed by the kendang code, intended to easy in learn it. Dance wardrobe designed by Siwi and Reki in considering doesn’t disturb the movement, and the choice in bright color of wardrobe was liked by children.